Uma's Social Capital in the 2024 Legislative Election in Mentawai - Sabaggalet, Yudas; Zulfa, Zulfa (Journal of Humanity Studies, 2024)
The Uma (Traditional House) social capital in Mentawai no longer wants to vote in accordance with the 2024 legislative election. Uma as social capital in Mentawai is the main basis for determining legislative election votes. The aim of this research is: to describe general social capital in the 2024 legislative elections in the Mentawai Islands district. This research method uses descriptive qualitative methods, collecting data by observation, interviews and documentation studies. The data analysis technique in this research is data reduction, data presentation and verification. The results of this research are as follows: uma in shaping social culture can no longer be expected in the 2024 legislative elections. Uma no longer wins one agreed candidate in clean. So the legislature who previously sat on the council no longer gets a vote in the district. This change is caused by external cultural influences, economic influences, this is because everyone feels they have their own interests. The unity between cleans no longer exists. Uma's increasingly low social capital, political capital and economic capital have resulted in the failure of legislative candidates to sit in the Mentawai district government chair. Uma's social capital is not always a victory in the legislative elections. This shift is caused by Uma no longer being clean for society anymore. Uma is considered to no longer play a role and social and cultural capital is no longer supported in the Mentawai Islands. Uma's social and cultural capital is important in restoring strength to society for the future if it is used as a conservation site in the Mentawai Islands.